Skin Stem Cells as an Object for Cryopreservation. 1. Skin Stem Reserve - Volkova, Nataliya A.; Mazur, Svetlana P.; Kholodnyy, Vitaliy S.; Petrenko, Aleksandr Yu. (Problems of Cryobiology and Cryomedicine, 2014)
The review contains the data on scope, properties and localization of resident stem/progenitor cells of skin. The emphasis is given to populations of epithelial and dermal stem cells (SCs), as well as of melanocyte and subcutaneous fat SCs. The cells represent a prospective object for cryobiological technologies and establishing low temperature banks for use in theoretical and experimental biology, general and personalized medicine, development of bioengineered equivalents of tissues and artificial organs. Probl Cryobiol Cryomed 2014; 24(1):3–15.